Medicine Logistic Management: A Case Study at Sari Medika Pharmacy Malang - Aziz, Risqa Divacik Putri; Realita, Tasnim Nikmatullah; Rofiudin, M. (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
Medicine unavailability and expired of goods, and there's no medicine stock, excess medicine stock which will have retail and business consequences. The medicine logistic management problem that arose at Apotek Sari Medika Malang therefore, it need to evaluate for each process. The descriptive qualitative research aims to explore the theory and laws of medicine logistics management at Apotek Sari Medika Malang, which is appropriate to determine the availability of medicines in the pharmacy. Data collected by interviews with three informants. The results showed medicine logistics management at Apotek Sari Medika Malang has not been running effectively and efficiently. The conclusion is based on the input results such as insufficient medicine storage facilities and improperly implemented procedures according to laws of. The stage of the medicine selection process, the planning process for medicine procurement, procurement, receipt, storage, and control is still not effective, and finally. The output shows that Sari Medika Pharmacy is capable of sufficient medicine availability, but goods can still be found accumulating until death moving and expired date.